2006
DOI: 10.1111/j.1365-3040.2006.01615.x
|View full text |Cite
|
Sign up to set email alerts
|

Warm and cold parental reproductive environments affect seed properties, fitness, and cold responsiveness in Arabidopsis thaliana progenies

Abstract: Conditions in the parental environment during reproduction can affect the performance of the progenies. The goals of this study were to investigate whether warm or cold temperatures in the parental environment during flowering and seed development affect Arabidopsis thaliana seed properties, growth performance, reproduction and stress tolerance of the progenies, and to find candidate genes for progeny-related differences in stress responsiveness. Parental plants were raised at 20°C and maintained from bolting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 71 publications
4
70
0
2
Order By: Relevance
“…Similar findings have recently been reported for Arabidopsis (Arabidopsis thaliana; Blodner et al, 2007). There has been demonstrated the effect of temperature treatment memory on subsequent bud set and height growth in P. abies during somatic embryogenesis, thereby eliminating the influence of maternal effects per se (Kvaalen and Johnsen, 2008).…”
Section: The Progeny Of Infected Plants Exhibit Higher Resistance To supporting
confidence: 86%
“…Similar findings have recently been reported for Arabidopsis (Arabidopsis thaliana; Blodner et al, 2007). There has been demonstrated the effect of temperature treatment memory on subsequent bud set and height growth in P. abies during somatic embryogenesis, thereby eliminating the influence of maternal effects per se (Kvaalen and Johnsen, 2008).…”
Section: The Progeny Of Infected Plants Exhibit Higher Resistance To supporting
confidence: 86%
“…The detection of GUS activity in vegetative tissues is not totally unexpected. Indeed, it may be related to the environmental regulation of F3H (Pelletier and Shirley, 1996;Blö dner et al, 2007;Dubos et al, 2008;Zhang et al, 2011) and to counteracting chromatin-based regulation Schmitges et al, 2011). Consistent with this hypothesis, genome-wide analyses showed that in seedlings the F3H endogenous locus is largely enriched in H3K4me3, a mark usually associated with transcriptionally active chromatin .…”
Section: Rle Is Sufficient To Repress Transcriptional Activity and Ismentioning
confidence: 68%
“…Although empirical studies have only begun to investigate the link between epigenetic inheritance and environmental change, we know that increased temperatures can have positive transgenerational effects on germination rates, biomass, seed production, and thermal tolerance (Blödner et al, 2007). Theoretical work suggests that epigenetic inheritance can reduce lag times associated with within-generation plastic responses to environmental cues (Bonduriansky et al, 2012) and can introduce novel heritable phenotypic variation into populations with little genetic diversity (Pál and Miklós, 1999).…”
Section: Epigenetics and Evolutionary Adaptationmentioning
confidence: 99%